2019
DOI: 10.24908/ss.v17i3/4.8637
|View full text |Cite
|
Sign up to set email alerts
|

Watch Groups, Surveillance, and Doing It for Themselves

Abstract: This paper focuses on surveillant relations between citizens and police. We consider how online platforms enable the public to support the task of policing, as well as empowering the public to work without and beyond the police. While community-supported policing interventions are not new, more recently mobile and accessible technologies have promoted and enabled a DIY (Do-It-Yourself) culture towards policing amongst the public. The paper examines watch groups or those who task themselves with monitoring susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This scholarship has traced the growth of publicprivate intertwining, particularly following Stenning and Shearing's (1979) work on the growth of private security, which concluded that was almost impossible to identify functions or responsibilities of public police that were not in some ways being assumed by private actors. Studies on plural policing (e.g., Jones and Newburn 2006) have underlined the role of private actors in policing while also underlining how private actors are increasingly deputized into public policing apparatus particularly for surveillance functions (Mols and Pridmore 2019;Spiller and L'Hoiry 2019;Wakefield 2004). While earlier iterations of public/private policing research focused on the transfer of services from the public to private sector, our work contributes to research that is focused on the integration of public/private agencies.…”
Section: The High Policing Métier and Counterterrorism Trainings In C...mentioning
confidence: 99%
“…This scholarship has traced the growth of publicprivate intertwining, particularly following Stenning and Shearing's (1979) work on the growth of private security, which concluded that was almost impossible to identify functions or responsibilities of public police that were not in some ways being assumed by private actors. Studies on plural policing (e.g., Jones and Newburn 2006) have underlined the role of private actors in policing while also underlining how private actors are increasingly deputized into public policing apparatus particularly for surveillance functions (Mols and Pridmore 2019;Spiller and L'Hoiry 2019;Wakefield 2004). While earlier iterations of public/private policing research focused on the transfer of services from the public to private sector, our work contributes to research that is focused on the integration of public/private agencies.…”
Section: The High Policing Métier and Counterterrorism Trainings In C...mentioning
confidence: 99%
“…On the other hand, it is also a tool to channel that support, as police forces and individual police officers within them often hold varying views on the reliability of citizens, citing fears of vigilantism and other forms of 'cowboy-ish' behaviours when citizens are actively involved in neighbourhood watch groups (Pridmore et al 2018, 14). Therefore, the police prefers to be involved in such bottom up initiatives, often joining the WhatsApp conversation of a neighbourhood watch group, or keeping in close contact with moderators and other group leaders (Pridmore et al 2018, 12-16;Spiller and L'Hoiry 2018).…”
Section: Introductionmentioning
confidence: 99%